Linking Institutional Factors with the Financial Soundness of Banks. Evidence from the CEE Region - Šipilova, Viktorija; Meņšikovs, Vladimirs; Baltgailis, Jurijs (European Journal of Sustainable Development, 2023)
Sustainable financial sector needs the sound banking system. The soundness of the banking system is the subject for effects from institutional factors representing the areas of economy, society, public sector, legislation, technologies, and climate change. Although, studies rarely pay attention to the complex approach, where all areas are analysed simultaneously within the study. Design of the present study aims to analyse institutional factors of interdisciplinary nature, which demonstrate potential significance for the sound banking system. The authors focus on the cases that differ by the level of the soundness of banks. The approach provides the novelty of research. Method. During the research, the authors identify and characterise linkages between the factors of institutional environment and the soundness of banks. For the aim, monographic method and correlation analysis are applied. Analysis. The analysis is organised by using two cases that differ by the level of the soundness of banks – the region of Central and Eastern Europe and ten countries with the highest level of the soundness of banks in the world according to the data on Global Competitiveness Report. Results. For the cases that differ by the level of the soundness of banks, the research results demonstrate similarity by the linkages with indicators representing depth of financial system and corporate governance. Differences between the cases appear by the linkages with indicators representing public sector performance and stability of financial system. Conclusions. For the case with lower level of the soundness of banks, overall trends that are necessary for functioning of the sound banking system are observed. Although, several indicators that by their sense are significant for the sound banking system demonstrate negative direction or weak relationship with the soundness of banks what has to be improved in the future and appear as a result of the peculiarities of the banking sector in the region. Keywords: banks, financial soundness, institutions, factors, correlation.